Mechanism of contact pressure-induced friction at the amorphous carbon/alpha olefin interface - Li, Xiaowei; Wang, Aiying; Lee, Kwang-Ryeol (Nature Publishing Group | Shanghai Institute of Ceramics of the Chinese Academy of Sciences (SICCAS), 2018)
Combining an amorphous carbon (a-C) film with a lubricating oil can significantly improve the friction performance and lifetime of moving mechanical components. However, the friction mechanism is not well understood owing to a lack of information regarding the structure of the interface when exposed to high contact pressure. Here, we select linear alpha olefin, C5H10, as a lubricant and study the evolution of the structure of the a-C/C5H10/a-C sliding interface under contact pressure via reactive molecular dynamics simulation. Our results suggest that introducing C5H10 into the a-C/a-C interface reduces the friction coefficient by up to 93% compared with no lubricant, although the lubricating efficiency strongly depends on the contact pressure. In particular, increasing the contact pressure not only induces the binding of the lubricant with a-C, but also facilitates the dissociation of the C5H10 carboncarbon skeleton by specific scissions, which governs the friction behavior. These results disclose the underlying lubrication mechanism and could enable the development of new and effective lubricating systems with long lifetimes.